(untitled) (ELang | An English Language Education Journal, 2021)
The aims of the study are to know if Student Team Achievement Division (STAD) method effective for improving students’ reading comprehension on narrative text. And also, to know if the student like being taught in reading on narrative text through Student Team Achievement Division (STAD) method of the second-grade student of SMP PEMUDA BANJARAN. The sample of the research is 30 students. The method that was used in this research was pre-experimental design. The instrument are pre-test, post-test and questionnaire. The questionnaire is distributed to get students opinion the use of Student Team Achievement Division (STAD) method in teaching reading comprehension on narrative text. From this research, it was found that the value of t- that was higher than the t table (2.608 > 2.045) so that the Null Hypotheses (????o) is rejected and the Alternative Hypotheses (????????) is accepted. It means that Student Team Achievement Division (STAD) method is effective to improvement students reading comprehension on narrative text. Besides that, from the result of the questionnaire, students gave positive response and valuable contribution toward the use of STAD method in learning Narrative Text. It can be seen from the questionnaire given to them; they felt fun, like being taught using STAD method, they enjoyable, insightful, helpful, understandable, energic and they could visualize aspect of the text easily by STAD method. And they agreed that STAD method has detailed scoring system.